Condition of Coral Fish in Tapanuli Tengah Waters - Suharti, Sasanti Retno; Edrus, Isa Nagib (Oseanologi dan Limnologi di Indonesia, 2018)
Coral reefs is a center for biodiversity in the world with a complex architecture and has an aesthetics value. It also offers beneficial for human being in many aspects such as economics, social and culture. Research was conducted in July 2016 and aim to understand community structure and biomass of coral reef fishes in Tapanuli Tengah waters. Result from all stations in Tapanuli Tengah waters showed that 49 species from seven families of economically reef fish i.e.Â  Acanthuridae, Serranidae, Haemulidae, Lutjanidae, Lehtrinidae, Siganidae and Scaridae were found. Density average of those seven families was 163 individual/350 m2 or 4668 individual/ha with biomass average of 1.564 ton/ha. Moreover, biomass from other target fishes from nine families was accounted as 0.56 ton/ha. On the other hand, over all coralifore fish represented by Chaetodontidae was eight species from two genus, namely Chaetodon and Heniochus with four species. The density from family Chaetodotidae varies among station between 3-28 individual/350 m2